Insights into the catalytic mechanism of the chlorothalonil dehalogenase from Pseudomonas sp. CTN-3 - Yang, Xinhang; Diviesti, Karla; Miller, Callie; Bennett, Brian; Holz, Richard C. (Frontiers in Chemical Biology, 2023)
The catalytically competent Co(II)-loaded form of the chlorothalonil dehalogenase from Pseudomonas sp. CTN-3 (Chd, EC 3.8.1.2) was characterized by kinetic and spectroscopic methods. Maximum chlorothalonil (TPN; 2,4,5,6-tetrachloroisophtalonitrile) dehalogenase activity was observed in the presence of one Co(II) ion per monomer with kcat and Km values of 12 ± 3 s−1 and 130 ± 10 μM, respectively, providing a catalytic efficiency (kcat/Km) of ∼9.2 × 104 M−1s−1. The dissociation constant (Kd) for Co(II) was determined to be 0.29 µM, and UV-Vis spectroscopy indicated the active site Co(II) ion resides in a penta-coordinate environment. EPR spectra of Co1-Chd contain at least three distinct signals, an MS = ± 1/2 signal with a ∼94 G 59Co hyperfine pattern centered at g1’ ≅ 6.7, a broader MS = ± 1/2 signal with g1’ ≅ 5.7, an MS = ± 3/2 signal with tentatively estimated parameters of g1’ ≅ 10.5 (gz = 2.75), A1(59Co) ≅ 110 G, and a high-field broad resonance at g3’ ≅ 1.8. Four substrate-analog inhibitors with IC50 values ranging from 110 μM to 19 mM were also identified and characterized. Upon the addition of each of the substrate-like inhibitors to Co1-Chd, changes in the EPR spectrum were observed that, in all cases, were simpler than that of Co1-Chd in the absence of inhibitors and could be simulated as either a single species or a mixture of two. Simulation of these data indicate that the corresponding EPR signals are each due to a ground state MS = 1/2 Kramers’ doublet and are consistent with pentacoordinate Co(II) with a relatively constrained coordination sphere. These data suggest that the nitrile moiety of TPN may not directly coordinate to the active site metal ion, providing new insight into the catalytic mechanism for Chd.